Accountability: A Necessity to Pro-Poor Service Delivery in Municipal Councils in Uganda - David Mwesigwa; Ibrahim Abiodun Oladapo (Journal of Governance and Accountability Studies, 2021)
Purpose: This study examines the role of political accountability in improving pro-poor service delivery amid the growing challenges faced by Local Governments in Uganda. Research methodology: Using five Focus group discussions, perspectives on accountability are debated as a foundation for improving service delivery. Results: The findings revealed that accountability in Ugandan municipalities is influenced by performance standards, answerability, and sanctions or rewards. Conclusions: This study concludes that effective and inclusive accountability involving multi-stakeholder participation, community engagement, and strong institutional commitment is essential for improving pro-poor service delivery in Ugandan Municipalities. Limitations: The study covers only Uganda and may not easily be generalised to other countries. Contributions: The study contributes to knowledge so that hands-on accountability holds potential and requires more consideration as a means to assimilate learning-based methods and role-players network to back up the delivery of pro-poor services. Novelty: The novelty of this study lies in its emphasis on both formal and informal accountability mechanisms as integrated.